Ag–Cu solid–liquid interface velocity and growth morphology dependence on material data variations under rapid solidification conditions - D. Cietek; R. J. Hebert (Philosophical Magazine Letters)
This work aims at determining the effect that variations in material data have on predictions of growth morphologies for the Ag-Cu system. The predictions are based on the Kurz-Giovanola-Trivedi (KGT) model, which establishes quantitative relations between the solid-liquid interface velocity, alloy composition, and interface temperature. These relations can be used to predict the growth morphology for constrained growth conditions. Material data were extracted from the available literature to calculate the morphology changes for Ag-5wt% Cu. When considering the range of reported values of this alloy for the interface energy, melting entropy, liquid diffusion coefficient, and the characteristic system length, the transition from cellular to plane-front growth at high solidification velocities – commonly denoted as the absolute stability limit – could occur as low as 0.07 m/s or as high as 1.17 m/s. These predictions based on the KGT model are combined with experimental laser glazing of arc-melted buttons to identify melt-pool microstructures. Button cross-sections were glazed at 400 W with scan speeds of 0.1–0.3 m/s to demonstrate the accuracy of the model. The resulting microstructures are analysed from cross-sections using scanning electron microscopy. The predictions approximately match experimental observations of the absolute stability limit when median material property values are used. It is concluded that the large range of predicted laser velocities for absolute stability suggest that new approaches will be required if the analytical models should help guide additive manufacturing processing. In the meantime, the models are useful for predicting trends, for example, for alloy- or additive manufacturing technology selection.